Nurses’ Competence in Safety Blood Transfusion: The Impact of a Training Module (International Journal of Nursing Education, 2021)
The Aim: The aim of this study was to evaluate the effectiveness of a training module about safety bloodtransfusion on nurses’ competence. Methods: Pre experimental one group pre and post-test design wasadopted. The study was conducted at the hematology department in Oncology Center Mansoura UniversityHospital. A convenient sample of 60 staff nurses were included. Data were collected by a structured interviewquestionnaire to assess nurses’ knowledge level and observation checklist to assess nurses’ practices pre,and post-blood transfusion training. Data were analyzed by using both descriptive and inferential statistics.Results: Revealed a highly statistically significant difference in the mean score of the nurses’ knowledgelevel and practice about safe blood transfusion pre and post the training intervention (p=0.001). There wasa strong positive relation between nurses’ knowledge and practices scores post-training (r=0.745, P
Keywords: Nurses’ Competence, Safety Blood Transfusion, Training module.